Clinical relevance of tumor infiltrating lymphocytes, PD-L1 expression and correlation with HPV/p16 in head and neck cancer treated with bio- or chemo-radiotherapy. (2nd September 2017) - Ou, Dan; Adam, Julien; Garberis, Ingrid; Blanchard, Pierre; Nguyen, France; Levy, Antonin; Casiraghi, Odile; Gorphe, Philippe; Breuskin, Ingrid; Janot, François; Temam, Stephane; Scoazec, Jean-Yves; et al.
ABSTRACT: To investigate the prognostic value of tumor infiltrating lymphocytes (TILs: CD8+ and FoxP3+), and PD-L1 expression in patients with head and neck squamous cell carcinoma (HNSCC) treated with radiotherapy combined with cisplatin (CRT) or cetuximab (BRT). Immunohistochemistry for CD8, FoxP3 was performed on pretreatment tissue samples of 77 HNSCC patients. PD-L1 results were evaluable in 38 patients. Cox regression analysis was used to analyze the correlations of these biomarkers expression with clinicopathological characteristics and treatment outcomes. High CD8+ TILs level was identified in multivariate analysis (MVA) as an independent prognostic factor for improved progression-free survival with a non-significant trend for better overall survival (OS). High FoxP3+ TILs and PD-L1+ correlated with a favorable OS in the uni-variate analysis, respectively, but not in the MVA. In subgroup analysis, CD8+TILs appear to play a pivotal role, p16+/high CD8+TILs patients had superior 5-year OS compared with p16+/low CD8+TILs, p16-/ high CD8+TILs, and p16-/ low CD8+TILs patients. p16+/PD-L1+ patients had improved 3-year OS compared with p16+/PD-L1-, p16-/ PD-L1+, and p16-/ PD-L1- patients. In low CD8+ TILs tumors, 5-year loco-regional control of patients treated with CRT was improved vs. those with BRT (p = 0.01) while no significant difference in high CD8+ TILs was observed. CD8+ TILs correlated with an improved clinical outcome in HNSCC patients independent of Human papillomavirus status. The immunobiomarkers may provide information for selecting suitable patients for cisplatin or cetuximab treatment. Additionally, the impact of TILs and PD-L1 of deciphering among the p16+ population a very favorable outcome population could be of interest for patients tailored approaches.